A survey of physical layer security in space-air-ground communication and networks - Fuchao YAN; Yiliang LIU; Shuai HAN; Weixiao MENG (Dianxin kexue)
Space-air-ground communication and networks are the trend of wireless communication in the future.Because of its inherent broadcast nature and wide coverage,its communication and network systems will face serious security problems.How to ensure the security of space-air-ground communication and networks is an urgent problem to be solved.As an effective means of security,physical layer security technology has attracted more and more attentions.The basis of physical layer security and the channel model of space-air-ground communication and networks were introduced,and then the common technologies in physical layer security were introduced and summarized,such as wiretap coding,beamforming and artificial noise,relay cooperation interference and physical layer key generation,finally the challenges and future development trend of physical layer security in space-air-ground communication and networks were proposed.